2017
DOI: 10.17507/tpls.0705.08
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Student’s Ability in Writing at Riau University Pekanbaru - Indonesia

Abstract: Abstract-This study focused on the analysis of students' writing performance. It aimed to ascertain the students' ability in using grammar, vocabulary, punctuation, spelling, coherence and cohesion. To measure the students' writing ability, they were told to do a writing task to be completed in less than 75 minutes in duration. The task asked them to imagine that they were working for a company in Batam, a fast-growing administrative town in Kepulauan Riau Province. They were told to write a letter to their fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 3 publications
2
21
1
1
Order By: Relevance
“…As a result, a good cohesive and coherence on their essay writing are not existed since they perceived the cohesive and coherence problems (Ahmed, 2010;Belkhir & Benyelles, 2017;and Ariyanti & Fitriana, 2017). Further, the grammatical problems were also experienced by the EFL students in essay writing (Ariyanti & Fitriana, 2017;Hasan & Marzuki, 2017;and Nasser, 2019) covering plural forms, articles, verbs forms, clauses, passive voice and preposition. Furthermore, the mechanics problems of punctuation, spelling, handwriting also faced by the EFL students in their essay writing (Ariyanti &Fitriana, 2017 andNasser, 2019).…”
Section: E Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, a good cohesive and coherence on their essay writing are not existed since they perceived the cohesive and coherence problems (Ahmed, 2010;Belkhir & Benyelles, 2017;and Ariyanti & Fitriana, 2017). Further, the grammatical problems were also experienced by the EFL students in essay writing (Ariyanti & Fitriana, 2017;Hasan & Marzuki, 2017;and Nasser, 2019) covering plural forms, articles, verbs forms, clauses, passive voice and preposition. Furthermore, the mechanics problems of punctuation, spelling, handwriting also faced by the EFL students in their essay writing (Ariyanti &Fitriana, 2017 andNasser, 2019).…”
Section: E Discussionmentioning
confidence: 99%
“…Ariyanti & Fitriana (2017) reported that Indonesian EFL university students were trouble in using grammar, cohesion, coherence, paragraph organization, diction, and spelling errors in essay writing. Additionally, Hasan & Marzuki (2017) analyzed the Indonesian EFL students' ability in writing by asking the students to do writing task in determined time. Their findings showed that the grammatical problems covering using plural forms, articles, verbs forms, clauses, passive voice and preposition existed on the students' writing.…”
Section: A Introductionmentioning
confidence: 99%
“…It tended to how the participant constructed the sentence to be, for example simple, compound, or complex sentences. Moreover, the rhetorical structure referred on how the texts were organized by following steps or pattern, such as applied by (Al Qahtani, 2006;Adnan, 2011;Hartley, 2008;Jalilifar, 2010;Jogthong, 2001) in analyzing the rhetorical structure in the research article introduction. Paper before applying TIF Paper after applying TIF Lexical sophistication The participant's writing showed some lexical sophistication in her research thesis, such as "the sentence ………………….…”
Section: Findings 41 Data Textsmentioning
confidence: 99%
“…However, the reality in Indonesia, despite students have been studying English from elementary school, many still struggle to write proper English essays. Hasan and Marzuki (2017) suggest that this is partly caused by the lack of practice along that learning period. They study that generally, English teachings in those level before university put more emphasis on reading and only give a small portion of attention in speaking and writing practice (productive skills).…”
Section: Introductionmentioning
confidence: 99%